CX3CR1(+) B Cells Show Immune Suppressor Properties - Wu, Zhiqiang (The Journal of biological chemistry, 2014)
The immune regulatory functions of B cells are not fully understood yet. The present study aims to characterize a subtype of B cells that expresses CX3CR1. In this study, peripheral blood samples were collected from patients with food allergies and healthy subjects. Peripheral B cells were analyzed by flow cytometry. T cell proliferation was assessed by carboxyfluorescein succinimidyl ester dilution assay. The results showed that the CX3CR1+ B cells were detected in the peripheral blood samples of healthy subjects and were significantly less in patients with food allergies. CX3CR1+ B cells expressed high levels of TGF-β and integrin αvβ6. CX3CR1+ B cells could efficiently suppress other effector CD4+ T cell activation. We conclude that human peripheral CX3CR1+ B cells have immune suppressor properties.